Learning path : Android : test-driven Android app development. - Mondal, Soham; Jones, Brandan; Safari eBooks ([Place of publication not identified] : Packt Publishing, 2016)
"Android Nougat is the 7th major version of the Android operating system. Test-driven development enables good design. It only makes sense to adopt it for Android N app development. This Learning Path covers the fundamentals of app development in Android N including the Android Studio and Android SDK, networking concepts with the API, Firebase analytics and crash analysis, and publishing your application on the Play Store . We will then look in detail how test-driven development can be implemented for building apps in Android. Leverage the power of test-driven development for building high-quality Android apps with this Learning Path."--Resource description page.
Android N application development / Soham Mondal -- Test-driven Android / Brandan Jones.
Presenters, Soham Mondal, Brandan Jones.
Title and publication information from resource description page (Safari, viewed April 5, 2017).
Keywords: Android (Electronic resource); Application software -- Development; Mobile apps; Electronic books